Salivary biotypes of mutans Streptococci levels in schoolchildren aging 6-8 year old having a socioeconomic base - Denise Madalena Palomari Spolidorio; José Francisco Höfling; Edvaldo Antônio Ribeiro Rosa; Cássio Vicente Pereira; Daniella Moreira; Reginaldo Bruno Gonçalves (Universidade Estadual de Campinas, 2015)
There is still little information on the mutans Streptococci biotypes in South America, specifically in Brazil, including regional and local information, associated to different socioeconomic categories. In this paper, the Streptococcus mutans levels and biotypes in Brazilian children aged 6-8 year old having a socioeconomic base was investigated. The sampling consisted of 200 selected children belonging to five different socioeconomic categories. Bacterial examination was made using children saliva diluted and cultivated in Bacitracin sucrose agar (SB-20). The plates were incubated by 48 hours/37ºC at 10% CO2 in anaerobiose and after colonies growth samples identification was performed by biochemical tests. Results showed that 78% of the 491 tested samples harbored S. mutans, followed by S. sobrinus (11.6%), S. rattus (4.69%), S. mutans V (2.65%), S. cricetus (1.83%) and S. ferus (1.22%). The prevalence of Streptococcus mutans was found in every socioeconomic level. Among children harboring multiple species, the most frequent association detected was S. mutans/ S. sobrinus (17%).